Vehicle Automation and the Duty to Act - Goodall, Noah (University of Virginia, 2014)
The act of driving always carries some level of risk. With the introduction of vehicle automation, it is probable that computer-driven vehicles will assess this changing level of risk while driving, and make decisions as to the allowable risk for itself and other road users. In certain situations, an automated vehicle may be forced to select whether to expose itself and its passengers to a small risk in order to protect other road users from an equal or greater amount of cumulative risk. In legal literature, this is known as the duty to act. The moral and legal responsibilities of an automated vehicle to act on the behalf of other road users are explored.
Original submission date: 2020-10-30T14:29:45Z